The Influence of Information Technology, Work Environment, and Work Efficiency on Employee Performance (A Case Study of Employees at PT Permodalan Nasional Madani in Pati City) - Apriliana, Kartika Maulida; Kusdiyanto, Kusdiyanto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the influence of Information Technology, Work Environment, and Work Efficiency on Employee Performance at PT Permodalan Nasional Madani in Pati City. The method used is quantitative, with primary data collected through a questionnaire distributed to 140 employees. The data were analyzed using statistical analysis with Partial Least Squares (PLS) Structural Equation Modeling (SEM) utilizing SmartPLS 3.0. The results of the study indicate that Information Technology does not have a significant effect on employee performance (t-statistic = 1.415; P value = 0.079), leading to the rejection of the first hypothesis (H1). Conversely, the Work Environment has a positive and significant impact on employee performance (t-statistic = 2.372; P value = 0.009), resulting in the acceptance of the second hypothesis (H2). Additionally, Work Efficiency also demonstrates a positive and significant effect on employee performance (t-statistic = 5.079; P value = 0.000), thereby accepting the third hypothesis (H3). This study concludes that to enhance employee performance, the company should focus on developing a positive work environment and improving work efficiency, as well as investing in supporting technologies.